Lowest Excited-State Impurity Binding Energy in InGaN/GaN Parabolic QWW: Magnetic Field Effect - El Ghazi, Haddou; Jorio, Anouar; Zorkani, Izeddine (Communications in Physics, 2013)
In this paper, we have investigated the magnetic field effect on the lowest excited-state binding energy of hydrogenic shallow-donor impurity in wurtzite (In,Ga)N/GaN parabolic transversal-section quantum-well wire (PQWW) using the finite-difference method within the quasi-one-dimensional effective potential model. The calculations are performed within the framework of the effective mass approximation. A cylindrical QWW effective radius is taken into account to describe the lateral confinement strength. The numerical results show that: (i) the probability density is the largest on a circularity whose radius is the effective radius and (ii) the lowest excited-state binding energy is the largest when an impurity is located on this circularity while it starts to decrease as the impurity is away from the circularity.